*‐Predictable MPSoC execution of real‐time control applications using invasive computing. (3rd February 2019) - Brand, Marcel; Witterauf, Michael; Sousa, Éricles; Tanase, Alexandru; Hannig, Frank; Teich, Jürgen
Summary: The fulfillment of non‐functional requirements like timing or energy consumption is of utmost importance in many embedded systems and respective applications. Especially, with the introduction of multi‐core architectures, the ability to predict non‐functional execution qualities becomes more and more difficult, as multiple concurrent application programs may interfere in execution when typically sharing all the resources. In this paper, we advocate a novel parallel computing paradigm called invasive computing that allows to isolate application programs on multi‐core targets. For a presented case study of a cyber‐physical real‐time control system, we show that invasive computing enables composability that in fact allows to characterize and analyze each application program statically and independent from each other. More specifically, it is shown that a distributed object detection algorithm for controlling an inverted pendulum and implemented on a heterogeneous invasive multi‐processor SoC (MPSoC) is able to provide real‐time guarantees as well as reliability requirements on demand.